(untitled) (LACCEI, 2024)
Oily Sludge (OS) is a complex combination of oil and water emulsions with suspended solid impurities. They have high viscosity and stable emulsions that prevent the sedimentation of solid components. It is estimated that one ton of crude oil produces between 0.3% and 0.5% of OS. Pyrolysis is a process in which the raw material is heated to high temperatures (400-1000°C) in an oxygen-free reactor or an anoxic atmosphere. This causes the breakage of the C-C and C-H bonds in the compound, producing lighter hydrocarbons in the form of condensed liquids or non-condensable gases. In the end, a combination of carbon, liquid, and gases is obtained, depending on the operating conditions of the pyrolysis. Vacuum pyrolysis was carried out on a sample of oily sludge (OS) originating from oil production operations in Oilfield IX in Talara, Peru. The yield of liquid, solid, and gaseous products was evaluated, and the fraction of liquid hydrocarbons was characterized. The best results were achieved at a temperature of 550°C and a pressure of 31.33 kPa abs. The yield of liquid products (crude and water) was 81.4%, while the yield of solid products reached 10.3% and the yield of gases was 8.3%. The liquid hydrocarbon obtained under these conditions has a density of 864 kg/m3, a viscosity of 6.88 cSt at 50°C, and a higher calorific value of 40.16 MJ/kg.